2017
DOI: 10.1111/apa.13956
|View full text |Cite
|
Sign up to set email alerts
|

A review of important electroencephalogram features for the assessment of brain maturation in premature infants

Abstract: This review describes the maturational features of the baseline electroencephalogram (EEG) in the neurologically healthy preterm infant. Features such as continuity, sleep state, synchrony and transient waveforms are described, even from extremely preterm infants and includes abundant illustrated examples. The physiological significance of these EEG features and their relationship to neurodevelopment are highlighted where known. This review also demonstrates the importance of multichannel conventional EEG moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 56 publications
0
51
0
Order By: Relevance
“…In seizure-related studies, it was found that both aEEG and conventional EEG may help to detect seizures, as well as allowing monitoring of the effect of treatment with antiepileptic drugs, analysis of background activity of the EEG and the characterization of diagnoses and prognostics 38 . However, with the low number of channels, not all seizures are detectable by aEEG 34,37 . Other studies have suggested the use of video-EEG to allow the analysis and validation of abnormal movements, such as epileptic seizures, and the location of the origin of possible artifacts 24,38 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In seizure-related studies, it was found that both aEEG and conventional EEG may help to detect seizures, as well as allowing monitoring of the effect of treatment with antiepileptic drugs, analysis of background activity of the EEG and the characterization of diagnoses and prognostics 38 . However, with the low number of channels, not all seizures are detectable by aEEG 34,37 . Other studies have suggested the use of video-EEG to allow the analysis and validation of abnormal movements, such as epileptic seizures, and the location of the origin of possible artifacts 24,38 .…”
Section: Discussionmentioning
confidence: 97%
“…Although it has problems related to its interpretation, when used by experienced clinicians, aEEG has been shown to be of great relevance in providing an overview of conventional EEG activity 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amplitude of the activity between bursts increases gradually and the proportion of bursts and the duration of activity periods also increase. These patterns are summarised as background EEG activity and provide important information related to maturation and prognosis after an insult (4,(19)(20)(21)(22)(23).…”
Section: Analysis and Interpretationmentioning
confidence: 99%
“…This review by Pavlidis et al. describes the maturational features of the baseline electroencephalogram (EEG) in the neurologically healthy preterm infant . Features such as continuity, sleep state, synchrony and transient waveforms are described also in extremely preterm infants.…”
Section: Important Eeg Features For the Assessment Of Brain Maturatiomentioning
confidence: 99%